Stability indicating chromatographic techniques for the determination of pipoxolan HCl - Hala E. Zaazaa, Afaf O. Mohamed, Mohamed Abdelkawy and Maha A.Hawwam (Journal of Applied Pharmaceutical Science, 2013)
Two simple, accurate and sensitive methods were developed for the determination of pipoxolan HCl in presence of its degradation product. HPLC method (A), performed on C18 column using acetonitrile: 1mM ammonium acetate (80:20 v/v) as a mobile phase with a flow rate of 1.8ml/min. Detection was performed at 210 nm. TLC-densitometric method (B), using silica gel 60 F254 plates; the optimized mobile phase was chloroform: toluene: methanol: 10% ammonia (6:5:3:0.1 v/v). Quantitatively the spots were scanned densitometrically at 210 nm. Linearity ranges were 1-10 μg/ml for method A and 2-20 μg/band for method B, with mean percentage recoveries 99.38±0.672% and 99.32±0.97% for methods A and B, respectively. The proposed methods were found to be specific for pipoxolan HCl in presence of up to 90% of its degradation product. Statistical comparison between the results obtained by these methods and the manufacturer’s method was done,and it was found that there was no significant differences between them.
Keywords: Pipoxolan HCl, HPLC, TLC-densitometric, Stability.